Migrants' rights, populism and legal resilience in Europe - Stoyanova, Vladislava; Smet, Stijn (Cambridge University Press, 2022)
Bringing together scholars of migration and constitutional law, this volume analyses the problematic relationship between the rise of populism, restrictions of migrants' rights and democratic decay in Europe. By offering both constructive and critical accounts, it creates a nuanced debate on the possibilities for and limitations of legal resilience against populist erosion of migrants' rights. Crucially, it does not merely diagnose the causes of restrictions of migrants' rights, but also proposes how the law might be used as a solution. In this volume, the law is considered as both a source of resilience and part of the problem at three distinct levels: the legal-theoretical, the European, and the national level. It is a major contribution to the literature on migrants' rights, offering a nuanced account of how legal resilience might be used to safeguard migrants' rights against further erosion in populist times. This book is available as Open Access.